Legal Regulation of “Smart City” Technologies in the Context of Digitalization - Zarina K. Kondratenko; Lidiya L. Sabirova; Nikita S. Vavilov (Communications of International Proceedings, 2021)
The article analyzes the regulatory legal acts of the Russian Federation regulating the current process of digitalization in the field of urban economy, the economy of a municipal formation, building a dialogue between authorities and the population of a particular municipal formation. The practice of individual municipalities in introducing smart city digital technologies into their activities is considered. The article provides a definition of such a phenomenon as a smart “city”, identifies trends in legal regulation in this area. The purpose of this article is a comprehensive study of the legal regulation of smart city technologies in the context of digitalization in the Russian Federation. The methodological basis of the study is a set of methods for the scientific cognition of social processes, circumstances and facts. The research is based on the methodological principles of objectivity, determinism, historicism, integrity, complexity, consistency, structure, functionality, hierarchy, pluralism of explanation and understanding of law, comparative studies. The work was carried out through the methods of dialectical materialism as a fundamental tool in humanitarian research. It should be noted the use of such general scientific methods as analysis, synthesis, deduction and induction in the work. The research results were tested in the process of teaching and educational activities.
Keywords: Smart City; Digital Economy; Municipal Formation; Digitalization; Legal Regulation; Digital Technologies; Municipal Law.